THE METHODOLOGY OF EDUCATING HIGH SCHOOL STUDENTS IN THE SPIRIT OF LOYALTY TO MORAL VALUES - Eshqoʻziyeva Muhayyo Ermat qizi, (TADQIQOTLAR, 2026)
Abstract: The education of high school students is a critical period that greatly impacts the  formation  of  their personalities, worldviews, and attitudes  towards  life itself. Particularly in a rapidly changing global society, the role of instilling loyalty to moral  values  becomes  increasingly  essential  for  guiding  adolescents  through  the challenges  and  choices  they  are  faced  with.  The  methodology  for  cultivating  such loyalty requires a well-structured, holistic, and consistent approach that addresses the intellectual, emotional, and behavioral domains of the student’s development.